TEKNOLOGI INFORMASI DAN PERTUMBUHAN UMKM: SEBUAH PENELITIAN AWAL - Maresti, Fahra Muftia; Pratama, M Andrean; Saputra, Tedy Setiawan (STIE Semarang, 2024)
This research explores the influence of Information Technology on the growth of Micro, Small, and Medium Enterprises (MSMEs) in Palembang City. Through qualitative methods and a literature study of 11 journal articles, it was found that Information Technology has a significant positive impact on the development of MSMEs. Information Technology facilitates various aspects of MSME operations, including sales, promotion, communication, and information dissemination. Data shows that internet usage in Palembang reached 1,430,087 people, while the number of MSMEs in South Sumatra reached 860,000 businesses. However, there is a decrease in the number of MSMEs in Palembang City from 8,881 in 2019 to 7,500 in 2020. This research highlights the importance of Information Technology adoption for the sustainability and growth of MSMEs, and underscores the need for more effective strategies to support MSMEs in the digital era.